Effect of Ketogenic Diet In Obese Patients With Type 2 Diabetes: A Systematic Review - Juliska, Shelly; Anita Rahmiwati; Novrikasari (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
ABSTRACT Background : Diabetes is non communicable diseases and fastest growing diseases worldwide, that cause many complications, lead to increased mortality and decreased quality of life in individuals. Diabetes complications can controlled by dietary intervention. Ketogenic Diet (KD) is one of trusted method that having beneficially effects for patients with Type 2 Diabetes Mellitus (T2DM) . Objective : This paper aim to investigate the effect of KD in the patients T2DM. Methods : This paper used the systematic review. Articles are selected using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analysis) based on google scholar and PubMed. The inclusion criteria in this writing are articles published within the last 5 years with keywords â€œKetogenic Diet, Type 2 diabetes, clinical trialâ€ Result : The results show that KD had significantly beneficial effects on weight, Body Mass Index, Cholesterol, Blood Sugar, Fasting Insulin and HbA1c were decrease and quality of sleep were increased after intervention (p value < 0,001) Conclusion : KD can controlled the body weight, blood glucose, lipids and also good for increased sleep quality in patients T2DM but have a low adherence for long term persistence Keywords : Ketogenic diet, type 2 diabetes, clinical trial